2011
DOI: 10.1523/jneurosci.0623-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Necessity is the Mother of Invention: Reconstructing Missing Sensory Information in Multiple, Concurrent Reference Frames for Eye–Hand Coordination

Abstract: When aligning the hand to grasp an object, the CNS combines multiple sensory inputs encoded in multiple reference frames. Previous studies suggest that when a direct comparison of target and hand is possible via a single sensory modality, the CNS avoids performing unnecessary coordinate transformations that add noise. But when target and hand do not share a common sensory modality (e.g., aligning the unseen hand to a visual target), at least one coordinate transformation is required. Similarly, body movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 45 publications
6
70
1
Order By: Relevance
“…pointing with one hand to the other) and even when no visual feedback about the hand is allowed [1][5]. This is in apparent contrast with our own studies on human sensori-motor integration [6], [7] in which we observed that if subjects were asked to align their hidden hand to the orientation of a kinesthetically felt target, they completely ignored the information related to the visual scene, indicating that the brain executes purely kinesthetic tasks (K-K: kinesthetic target and kinesthetic response) without using a visual representation of the movement. This apparent contradiction, however, could be related to a fundamental difference between the motor tasks that the subjects were asked to perform in these different sets of studies.…”
Section: Introductioncontrasting
confidence: 77%
See 2 more Smart Citations
“…pointing with one hand to the other) and even when no visual feedback about the hand is allowed [1][5]. This is in apparent contrast with our own studies on human sensori-motor integration [6], [7] in which we observed that if subjects were asked to align their hidden hand to the orientation of a kinesthetically felt target, they completely ignored the information related to the visual scene, indicating that the brain executes purely kinesthetic tasks (K-K: kinesthetic target and kinesthetic response) without using a visual representation of the movement. This apparent contradiction, however, could be related to a fundamental difference between the motor tasks that the subjects were asked to perform in these different sets of studies.…”
Section: Introductioncontrasting
confidence: 77%
“…in a replication of the K-K condition of our previous study [6]) and we compared their responses in two different conditions (Figure 1). In the first, called INTRA-manual, subjects memorized and reproduced the orientation with the same hand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that the 'mode of control' of reaching movements to a visual target depends on whether only proprioceptive information about the hand position can be used, or whether vision is also available (Krakauer et al, 1999;Reichenbach et al, 2009). The latter allows for directly relating visual target and hand position in a common reference frame (Tagliabue and McIntyre, 2011), and different neural circuits may be recruited dependent on the mode of control (Bernier et al, 2009). Recent fMRI studies have assessed the relative contribution of different PPC areas to the processing of visual and proprioceptive information during motor control, mainly by investigating brain activity during the whole movement (Bernier and Grafton, 2010;Blangero et al, 2009;Filimon et al, 2009;Pellijeff et al, 2006), in which different temporal stages of movement control can hardly be disentangled.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, it is believed that all sensory signals have to be converted into a common frame of reference (Buneo & Andersen, 2006;Cohen & Andersen, 2002;Engel, Flanders, & Soechting, 2002;Knudsen, du Lac, & Esterly, 1987;Lacquaniti & Caminiti, 1998;Soechting & Flanders, 1989). However, reference frame transformations can induce noise that depends on the size of the transformation required (Blohm & Crawford, 2007;Burns & Blohm, 2010;Soechting & Flanders, 1989;Tagliabue & McIntyre, 2011;van Beers, Baraduc, & Wolpert, 2002).…”
Section: Introductionmentioning
confidence: 99%